Analisis Kebutuhan Pembelajaran Beridiferensiasi Pada Mata Pelajaran Pendidikan Pancasila - Melandhany, Mareta; Winarno; Noventari, Widya (University of Muhammadiyah Malang, 2024)
The implementation of the Independent Curriculum moves schools with learning that is pro-student. SMA Al Islam 1 Surakarta is a driving school that implements the Independent Curriculum and seeks to implement differentiated learning. This study aims to analyze the learning needs of differentiated Pancasila education subjects at SMA Al Islam 1 Surakarta. This research is a descriptive research with a qualitative approach. Sources of research data include teachers of the Pancasila Education subject and students at SMA Al Islam 1 Surakarta. Data collection techniques with observation techniques, interviews, and documents. The qualitative data validity test was carried out by triangulation. Qualitative data analysis techniques with triangulation of sources and methods. The results of the study show an analysis of learning styles, using learning style data obtained from schools which are the results of measurements from the school in collaboration with the psychology team. Initial ability analysis showed that the results of the pre-test carried out by 73 students got an average score of 58.5. Analysis of the needs of the development of differentiated learning, the teacher has analyzed the needs and ensured the readiness of students. Meanwhile, students still have difficulties if the learning material is not explained in detail. Analysis of the needs for the development of teaching modules, the teacher arranges teaching modules according to the procedures and components of the teaching modules. The results of the document study show that there is a content component that is lacking.